Creative Hyperfidelity and Finnegans Wake: Reflections on the Translation of Joyce’s Criticism of Racist and Nazi Discourse - Martins, Claudia Santana (ABEI Journal, 2017)
Finnegans Wake, by James Joyce, is one of the most complex and enigmatic works in literature. For scholars like Len Platt (2007) andVincent Cheng (1995), race is one of the central themes of this novel, which was a response to the nationalist and eugenicist discourse adopted by many right-wing thinkers and groups in the late nineteenth century and the first decades of the twentieth century, culminating with Nazism. In Finnegans Wake, Joyce satirised, by means of puns, portmanteau words and other hybrid constructions, the racial purity ideas then in vogue, as well as the Nazi ideology itself. The work proposed here aims to examine three complete translations of Finnegans Wake (two translations into French, one by Philippe Lavergne and the other by Hervé Michel; and one into Brazilian Portuguese, by Donaldo Schüler), in order to discuss the various solutions offered by the translators for transposing into French or Portuguese the passages in whichJoyce satirises the ideas of racial purity, scientific racism and Nazism. One of the purposes of this analysis is to reflect on the different possibilities of translating a multilayered, multilingual, and polysemous text like this while retaining as much as possible its political and historical references. The main question to be discussed is whether there is a translation technique that favours the rendering of this kind of reference.